Nitrate Handbook Environmental, Agricultural, and Health Effects - Tsadilas, Christos (Taylor & Francis, 2022)
Provides an overview of the entire nitrate cycle and the processes influencing nitrate transformation, and clearly identifies its role as an essential nutrient in plant growth, food preservation, and human health. It explains the discrepancies between public perceptions on nitrate harm versus the beneficial effects on human health.